2011
DOI: 10.22146/ijc.21419
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHOLIPIDS FROM PUMPKIN (<i>Cucurbita moschata</i> (Duch.) Poir) SEED KERNEL OIL AND THEIR FATTY ACID COMPOSITION

Abstract: The phospholipids (PL) of pumpkin (Cucurbita moschata (Duch) Poir) seed kernel and their fatty acid composition were investigated. The crude oil was obtained by maceration with isopropanol followed by steps of extraction yielded polar lipids. The quantitative determination of PLs content of the dried pumpkin seed kernel and their polar lipids were calculated based on the elemental phosphorus (P) contents which was determined by means of spectrophotometric methods. PL classes were separated from polar lipids vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Al-Khalifa (1996) noted that linoleic acid was the predominant fatty acid in C. moschata (53.2%) followed by oleic (26.2%), palmitic (13.1%) and stearic (6.0%). Raharjo et al (2011) reported that the predominant fatty acids associated with seed phospholipids were oleic and palmitic in phosphatidylcholine and phosphatidylethanolamine, and oleic and linoleic in phosphatidylserine. Fokou et al (2009) reported an average fatty acid composition (four varieties) of C. moschata as 49.5% linoleic, 19.6% oleic, 19.2% palmitic and 9.2% stearic with traces (1.7%) of arachidonic (C20:0) acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Khalifa (1996) noted that linoleic acid was the predominant fatty acid in C. moschata (53.2%) followed by oleic (26.2%), palmitic (13.1%) and stearic (6.0%). Raharjo et al (2011) reported that the predominant fatty acids associated with seed phospholipids were oleic and palmitic in phosphatidylcholine and phosphatidylethanolamine, and oleic and linoleic in phosphatidylserine. Fokou et al (2009) reported an average fatty acid composition (four varieties) of C. moschata as 49.5% linoleic, 19.6% oleic, 19.2% palmitic and 9.2% stearic with traces (1.7%) of arachidonic (C20:0) acid.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent reports, Applequist et al (2006) reported average fatty content values (four varieties) in C. moschata of 55.0% linoleic, 19.2% oleic, 15.8% palmitic and 6.9% stearic. Raharjo et al (2011) reported that the predominant fatty acids associated with seed phospholipids were oleic and palmitic in phosphatidylcholine and phosphatidylethanolamine, and oleic and linoleic in phosphatidylserine. Kim et al (2012) identified four fatty acids in the seed of C. moschata , these being linoleic (35.7%), oleic (31.3%), palmitic (12.8%) and stearic (7.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid composition is determined as the methyl esters of fatty acids by gas-liquid chromatography. Methyl esters of the fatty acids (FAME) of the three seed oils were prepared according to a convenient method [20], using BF3-methanol at 60 °C.…”
Section: Gc-ms Analysismentioning
confidence: 99%